Comparative study between SD BIOLINE Malaria Ag pf rapid diagnostic test and calibrated thick smear in the east region of Cameroon - Sylvie, Agokeng D.; Amandine, Mogou R.; Manyi, Ottop F.; Clement, Assob N. (International Journal of Scientific Research and Management (IJSRM), 2019)
In children of less than 59 months, Malaria is a public health problem, associated with an increased risk of mortality and morbidity. Thus, to improve the quality of the biological diagnosis of malaria, we made a comparative study for results of malaria test using the detection antigen HRP2 by SD bio line and calibrated thick smear. As participants, 204 patients admitted at the Bertoua regional hospital, biological diagnosis was based on the staining of the calibrated thick smear and the rapid diagnosis test SD BIOLINE Malaria Ag pf.The results of this study showed a good performance of the TDR SD BIOLINE Malaria Ag pf, 29(14.21 %) were TDR positive versus 32(15 .68%) for calibrated thick smear. the sensitivity, specificity, positive and negative predictive values of TDR compared to the calibrated thick smear were respectively (87 .5%, 99.41%, 97.71%, 96.55%) the limitations of RDT were shown with low parasitaemia. The cases of false positives were noted in patients who took drugs without prescription. At the end of our study, we suggested continuous use of RDTs in health centres to strengthen microscopy, which has a long analysis time and to strengthen the staff’s ability in management of malaria cases.